1998
DOI: 10.1086/515630
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-4 and Interleukin-5 Production in Response to Schistosoma haematobium Adult Worm Antigens Correlates with Lack of Reinfection after Treatment

Abstract: Acquired immunity to human schistosomiasis correlates with increased serum levels of schistosome antigen-specific IgE. Since interleukin (IL)-4 stimulates IgE production, the hypothesis that Th2-associated cell-mediated immunity participates in protection to reinfection was studied in a cohort of adolescent boys 12-18 months after chemotherapeutic cure in Upper Egypt. Initial Schistosoma haematobium prevalence was 51% and posttreatment incidence was 44%. Water contact was similar between putatively resistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 44 publications
6
63
1
Order By: Relevance
“…However, in the murine host, multiple vaccinations fail to boost cell-mediated immunity but progressively enhance the humoral arm of the protective response (13,31). Further evidence for the importance of type 2-mediated effector mechanisms comes from human patients, where a correlation exists between IL-4 and IL-5 production by PBMC and resistance to reinfection after drug treatment (40,53). It has to be noted that in humans, IgE and IgA antibodies have been postulated to participate in protective immunity (20,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the murine host, multiple vaccinations fail to boost cell-mediated immunity but progressively enhance the humoral arm of the protective response (13,31). Further evidence for the importance of type 2-mediated effector mechanisms comes from human patients, where a correlation exists between IL-4 and IL-5 production by PBMC and resistance to reinfection after drug treatment (40,53). It has to be noted that in humans, IgE and IgA antibodies have been postulated to participate in protective immunity (20,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the specific type of protective immune response generated by these antigens is frequently discordant between animal and human studies. Th1-type vaccine responses are frequently protective in murine models (33)(34)(35)46), while Th2-type responses are associated with resistance to reinfection in humans (19,32,39). This divergence makes generalizability from animal models of resistance problematic and underscores the importance of well-controlled, immunoepidemiology studies of schistosomiasis in humans.…”
mentioning
confidence: 99%
“…The association of Th2 responses and resistance to schistosome infection in humans has been observed for eosinophilia (24), anti-parasite IgE (17,19,38), and peripheral blood mononuclear cell (PBMC) production of interleukin-4 (IL-4) and IL-5 in response to crude parasite extracts (32,39). Despite broad acceptance of the paradigm, Th2 cytokine responses to specific parasite antigens have been prospectively associated with resistance to reinfection after PZQ treatment in only a single study in S. mansoni (3).…”
mentioning
confidence: 99%
“…However, more recent studies suggest that the situation is more complicated, showing that schistosome infections in mice with reduced type 2 responsiveness lead to a more severe pathological outcome than in mice capable of mounting type 2 responses [14]. In agreement with the more recent studies, immuno-epidemiological studies of human populations in endemic areas have revealed a positive correlation between high, specific immunoglobulin (Ig) E levels, eosinophilia, interleukin (IL)-5 levels and resistance to reinfection after treatment [30,48]. However, high levels of gamma interferon (IFN-γ) and tumor necrosis factor (TNF) together with lower levels of IL-5 seem to be associated with hepatosplenic disease [33].…”
Section: Introductionmentioning
confidence: 52%
“…Th2 responses, although related to hepatic fibrosis, seem to be associated with reduced susceptibility and host protection against overt human hepatosplenic disease due to inflammatory responses [25,30,33]. Indeed, also porcine IL-4 has been shown to play an important role in the regulation of macrophage mediated inflammatory responses [49].…”
Section: Discussionmentioning
confidence: 99%